RETRACTED ARTICLE: Protective role of arachidonic acid against diabetic myocardial ischemic injury: a translational study of pigs, rats, and humans - Yunhui Lv; Kai Li; Shuo Wang; Xiaokang Wang; Guangxin Yue; Yangyang Zhang; Xin Lv; Ping Zhao; Shiping Wang; Qi Zhang; Qiuju Li; Jinyan Zhu; et al. (Cardiovascular Diabetology)
Abstract Aim Patients with diabetes mellitus have poor prognosis after myocardial ischemic injury. However, the mechanism is unclear and there are no related therapies. We aimed to identify regulators of diabetic myocardial ischemic injury. Methods and results Mass spectrometry-based, non-targeted metabolomic approach was used to profile coronary sinus blood from diabetic and non-diabetic Bama-mini pigs at 0.5-h post coronary artery ligation. Six metabolites had a |log2 (Fold Change)|> 1.3. Among them, the most changed is arachidonic acid (AA), levels of which were 32 times lower in diabetic pigs than in non-diabetic pigs. The AA-derived products, PGI2 and 6-keto-PGF1α, were also significantly reduced. AA treatment of cultured cardiomyocytes protected against cell death by 30% at 48 h of high glucose and oxygen deprivation, which coincided with increased mitophagic activity (as indicated by increased LC3II/LC3I, decreased p62 and increased parkin & PINK1), improved mitochondrial renewal (upregulation of Drp1 and FIS1), reduced ROS generation and increased ATP production. These cardioprotective effects were abolished by PINK1(a crucial mitophagy protein) knockdown or the autophagy inhibitor 3-Methyladenine. The protective effect of AA was also inhibited by indomethacin and Cay10441, a prostacyclin receptor antagonist. Furthermore, diabetic Sprague Dawley rats were subjected to coronary ligation for 40 min and AA treatment (10 mg/day per animal gavaged) decreased myocardial infarct size, cell apoptosis index, inflammatory cytokines and improved heart function. Scanning electron microscopy showed more intact mitochondria in the border zone of infarcted myocardium in AA treated rats. Lastly, diabetic patients after myocardial infarction had lower plasma levels of AA and 6-keto-PGF1α and reduced cardiac ejection fraction, compared with non-diabetic patients after myocardial infarction. Plasma AA level was inversely correlated with fasting blood glucose. Conclusions AA protects against diabetic ischemic myocardial damage by promoting mitochondrial autophagy and renewal, which is related to AA derived PGI2 signaling. AA may represent a new strategy to treat diabetic myocardial ischemic injury.